Innovations in the designing and marketing of information services - Jeyasekar, J. John, 1965-; Saravanan, P., 1971- (Information Science Reference, 2020)
"This book examines the theoretical and practical aspects of improving and expanding information resources and services in a cost-effective way and enables librarians to plan and present information services for the betterment of civil society"--